Cardiovascular autonomic reactivity and inflammatory markers in patients with chronic migraine - Ayasha Nishad; Abhishek Tiwari; Waqas Alauddin; Prajakta Radke (Asian Journal of Medical Sciences, 2024)
Background: Common headache disorders, including tension-type migraines and cluster headaches, are related to malfunctions of the autonomic nervous system (ANS). Many autonomic signs of migraines aggravate the discomfort of the episode. Understanding the function and comorbidities of migraine patients depends on tests for assessing the cardiovascular autonomic responsiveness of the ANS. Aims and Objectives: The aim and objective of this study is to evaluate the use of cardiovascular reflex testing in adults with chronic migraine and healthy controls. Investigating inflammatory markers in individuals suffering from chronic migraines and controls. Materials and Methods: Thirty healthy controls and 30 people suffering from persistent migraines were part of the research. Cardiovascular reflex tests were performed. Inflammatory markers such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1, and IL-10 were also evaluated. SPSS edition 21 was used for the statistical analysis. For parameters with normal and atypical distributions, the Mann–Whitney test and the unpaired t-test, respectively, were used. Results: Among 30 subjects, testing for autonomic reactivity related to chronic migraines revealed significantly lower values than those for control. Patients with chronic migraines had far more inflammatory markers, including TNF-α, IL-1, and IL-10. Conclusions: Revealing autonomic dysfunction, the group with chronic migraines had a lower parasympathetic tone and sympathoexcitation than the healthy control group. Future studies should concentrate on ANS dysfunction as a biomarker for early warning signals for drug intake and migraine control.